Digital Marketing and Customer Trust Effects on Local Perfume Repurchase Intention via Purchase Decisions TikTok: Pengaruh Pemasaran Digital dan Kepercayaan Pelanggan terhadap Niat Pembelian Ulang Parfum Lokal melalui Keputusan Pembelian TikTok - Satria Danur Dara; Sri Mulyani; Emanuel M Bayudhirgantara (OGZ Research & Publishing, 2026)
Abstrak : Digital transformation in the trade industry encourages the use of social commerce platforms, such as TikTok Shop, as the main means of marketing local perfume products. This condition requires business actors to manage digital marketing strategies effectively and build consumer trust to improve the sustainability of purchasing behavior. This study aims to test the influence of digital marketing and customer trust on the repurchase intention of local perfume products with purchase decisions as an intervening variable in TikTok Shop users in the DKI Jakarta area. This study uses a quantitative approach with a survey method. Data was obtained through the distribution of online questionnaires to 167 respondents who had experience buying local perfumes at TikTok Shop. Data analysis was carried out using the Structural Equation Modeling method based on Partial Least Squares (SEM-PLS) with the help of SmartPLS software version 4.1. The test results show that digital marketing and customer trust have a positive and significant effect on purchase decisions. In addition, digital marketing, customer trust, and purchase decisions have also been proven to have a positive effect on repurchase intention. Purchase decisions play a significant role in mediating the influence of digital marketing and customer trust on repurchase intention. The value of the determination coefficient showed that digital marketing and customer trust were able to explain the variation in purchase decisions by 55.0%, while repurchase intention could be explained by 56.8% by all variables in the research model. These findings indicate that digital marketing optimization supported by consumer trust plays an important role in driving purchasing decisions and increasing sustainable repurchase intent on local perfume products..